Modern vibrational spectroscopy and micro-spectroscopy : theory, instrumentation, and biomedical applications - Diem, Max, 1947- (John Wiley & Sons, Inc., 2015)
Modern Vibrational Spectroscopy and Micro-Spectroscopy: Theory, Instrumentation and Biomedical Applications unites the theory and background of conventional vibrational spectroscopy with the principles of microspectroscopy. It starts with basic theory as it applies to small molecules and then expands it to include the large biomolecules which are the main topic of the book with an emphasis on practical experiments, results analysis and medical and diagnostic applications. This book is unique in that it addresses both the parent spectroscopy and the microspectroscopic aspects in one volume.- Resumé vydavatel
Keywords: spektrální analýza; vibrační spektra; vibrační spektroskopie; spectrum analysis; vibration spectra; vibration spectroscopy; elektronické knihy; monografie; electronic books; monographs